From Electrochemical Interface to Interphase (2D→3D) on Ionomer Membranes. Issue 3 (23rd December 2014) - Buchmüller, Yves; Hafner, Regina; Wokaun, Alexander; Schmidt, Thomas J.; Gubler, Lorenz
Abstract Polypyrrole (PPy) is introduced into proton exchange membranes via one‐sided polymerization to form a thin PPy/ionomer mixed layer, penetrating 1–10 μm into the bulk of the membrane. The proposed reaction mechanism enables variable thickness of the composite layer by adjustment of the synthetic parameters. The mixed layer extends the electrochemically active region from 2D (interface) to 3D (interphase). The created interphase allows detecting or triggering of electrochemical processes within the mixed ionomer/PPy zone. We present here an approach to electrochemically trigger two types of redox‐active species within the membrane: hydroquinone and a polymer‐bound phenolic compound (tyramine). The current response of the electrochemical process is increased by two orders of magnitude when comparing the 3D to the 2D configuration.